Dynamic shaking table test of a structural system made of a braced timber frame and low-density earth infill - Becerra, G.; Onnis, S.; Meli, G.; Wieser, M.; Tejada, U. (Springer Science and Business Media B.V., 2025)
There is a large deficit of housing and equipment in Latin America, which needs to be addressed with more construction alternatives offering seismic safety, in addition to economical, comfortable, and sustainable solutions. The proposal of a modular system of prefabricated elements of a braced timber frame structure and an infill made of panels of low-density earth is a feasible option for seismic-prone regions. This article describes a shaking table test performed on a proposed timber frame structure with a low-density earth infill and bracing of diagonal timber laths as part of a larger framework that seeks to propose a constructive solution. The test aims to assess the model’s seismic performance, determine its fragilities, and calculate the system’s dynamic properties. The seismic performance showed two stages of damage: an elastic stage during frequent and rare earthquakes, where the immediate occupancy and operational states of the structure were proven, and an over-resistance stage during a very rare earthquake, where life-safety performance with reparable damage was observed. The model’s dynamic properties showed an overall increase in damping related to the reduction of lateral stiffness, with the ability to deform and dissipate energy. Even though the system performed well, the test has shown some limits of the structure that should be considered for the construction of a future dwelling prototype.
Keywords: Light-frame timber buildings; Seismic performance; Shaking table test; Sustainable construction; Low-density earth infill; https://purl.org/pe-repo/ocde/ford#2.01.04